The complete ethical hacking series : honeypots, IDS and FW's - Russell, Chad; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"This course is for beginners and IT pros looking to get certified and land an entry level Cyber Security position paying upwards of six figures! Each chapter closes with exercises putting your new learned skills into practical use immediately. Honey drive - HoneyDrive is the premier honeypot Linux distro. It is a virtual appliance (OVA) with Xubuntu Desktop 12.04.4 LTS edition installed. It contains over 10 pre-installed and pre-configured honeypot software packages such as Kippo SSH honeypot, Dionaea and Amun malware honeypots, Honeyd low-interaction honeypot, Glastopf web honeypot and Wordpot, Conpot SCADA/ICS honeypot, Thug and PhoneyC honeyclients and more. Additionally it includes many useful pre-configured scripts and utilities to analyze, visualize and process the data it can capture, such as Kippo-Graph, Honeyd-Viz, DionaeaFR, an ELK stack and much more. Lastly, almost 90 well-known malware analysis, forensics and network monitoring related tools are also present in the distribution. Kippo - Kippo is a medium interaction SSH honeypot designed to log brute force attacks and, most importantly, the entire shell interaction performed by the attacker. Snort - Snort is an open-source, free and lightweight network intrusion detection system ( NIDS) software for Linux and Windows to detect emerging threats. DNSSec - Domain Name System Security Extensions (DNSSEC) is a suite of extensions that add security to the Domain Name System (DNS) protocol by enabling DNS responses to be validated. Specifically, DNSSEC provides origin authority, data integrity, and authenticated denial of existence."--Resource description page.
Title from resource description page (Safari, viewed January 3, 2018).
Presenter, Chad Russell.
Keywords: Computer security -- Examinations -- Study guides; Penetration testing (Computer security) -- Examinations -- Study guides; Hackers -- Examinations -- Study guides; Computer networks -- Security measures -- Examinations -- Study guides; Electronic books